2003
DOI: 10.1021/ic025944z
|View full text |Cite
|
Sign up to set email alerts
|

Aggregate Manganese Schiff Base Moieties by Terephthalate or Acetate:  Dinuclear Manganese and Trinuclear Mixed Metal Mn2/Na Complexes

Abstract: A reaction system consisting of terephthalic acid, NaOH, inorganic Mn(II) or Mn(III) salt, and salicylidene alkylimine resulted in dinuclear manganese complexes (salpn)(2)Mn(2)(mu-phth)(CH(3)OH)(2) (1, salpn = N,N'-1,3-propylene-bis(salicylideneiminato); phth = terephthalate dianion), (salen)(2)Mn(2)(mu-phth)(CH(3)OH)(2) (2, salen = N,N'-ethylene-bis(salicylideneiminato)), (salen)(2)Mn(2)(mu-phth)(CH(3)OH)(H(2)O) (3), and (salen)(2)Mn(2)(mu-phth) (4), while the absence of NaOH in the reaction led to a mononucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…A carboxylate-bridged dinuclear Mn(III) complex, in which the opposite coordination sites were capped by H 2 O and EtOH, exhibited a weak antiferromagnetic interaction (4.75μ B at 300 K, 3.82μ B at 5 K) [57]. Liu et al synthesized terephthalate-bridged dinuclear Mn(III) complexes [58]. By capping the opposite coordination sites with a MeOH molecule, discrete di-Mn(III) complexes were obtained: [{Mn III (SB)(MeOH)} 2 (-phth)] (SB = salen 2− and salpn 2− ) (Fig.…”
Section: Discrete Mn Complexesmentioning
confidence: 99%
See 2 more Smart Citations
“…A carboxylate-bridged dinuclear Mn(III) complex, in which the opposite coordination sites were capped by H 2 O and EtOH, exhibited a weak antiferromagnetic interaction (4.75μ B at 300 K, 3.82μ B at 5 K) [57]. Liu et al synthesized terephthalate-bridged dinuclear Mn(III) complexes [58]. By capping the opposite coordination sites with a MeOH molecule, discrete di-Mn(III) complexes were obtained: [{Mn III (SB)(MeOH)} 2 (-phth)] (SB = salen 2− and salpn 2− ) (Fig.…”
Section: Discrete Mn Complexesmentioning
confidence: 99%
“…Pecoraro et al first reported this type of compound using N,N -disalicylidene-2- there is a negligible magnetic interaction between the Mn(III) ions via the diamagnetic Na + ion, but there is a significant effect of anisotropy attributed to the Mn(III) ion (D = −6.13 cm −1 ) leading to a drop of χT at low temperature [59]. On the other hand, Liu et al [58] reported the presence of ferromagnetic exchange in the same core with the salpn 2− ligand (J = +1.74 cm −1 as H = −JS Mn1 S Mn2 ), where the decrease of χT was treated using the contribution of inter-molecular antiferromagnetic interactions (zJ = −0.125 cm −1 ) without taking into account the anisotropy of the Mn(III) ion. …”
Section: Discrete Mn Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Schiff base complexes have been extensively studied in great detail as a result of their prospective applications in catalysis, magnetic properties, molecular architectures and materials chemistry by coordination chemists at all times [3][4][5][6]. Numerous reports on metal-organic frameworks based on Schiff base ligands have been reported [7][8][9][10]. Recently, Schiff base complexes have also been found to present good nonlinear optical (NLO) property [11].…”
Section: Introductionmentioning
confidence: 99%
“…Network diversity of coordination polymers is currently under intensive exploration due to the important relationship between structures and properties as functional materials [1][2][3][4]. In the system of Cu 2+ / 4,4¢-bipy/salicylic acid, six networks covering 0-D, 1-D, 2-D, and 3-D were successfully constructed due to partly and fully deprotonated properties of the combination of hydroxyl and carboxylic groups [5][6][7], while for binary carboxylic acid, such as benzene-1, 4-dicarboxylic acid, networks with partly deprotonated ligands are sparse.…”
Section: Introductionmentioning
confidence: 99%